Structural Vibration Assessment of an Old Building Using Experimental Vibration Data - Ahmad Niza, Muhammad Aiman; Tuan Chik, Tuan Norhayati (Recent Trends in Civil Engineering and Built Environment, 2021)
Vibration may cause damage or reduce the serviceability of a building, especially for buildings that were constructed before vibration limits guideline was established. This study focuses on an old telecommunication building in Muar with the aim of assessing the vibration response of the building and whether the vibration is within the vibration limits as determined by the Department of Environment. A Finite Element Modelling is produced to simulate the building’s displacement and deformation under natural frequency and a series of test consisting of walking test and heel-drop test was performed on site to obtain the vibration response of the building in terms of acceleration, velocity and frequency. The maximum value for acceleration, velocity and frequency are 0.012 , 0.0003 m/s, and 6.641 Hz. According to the source guideline for the The Planning Guidelines for Vibration Limits and Control in the Environment which is DIN 4150-3, the peak vibration velocity is within the recommended limit for its frequency which is below 3 mm/s for the frequency range of 1 to 10 Hz.